A Study of Bone Mineral Density and Its Determinants in Type 1 Diabetes Mellitus - Ameya Joshi; Premlata Varthakavi; Manoj Chadha; Nikhil Bhagwat (Journal of Osteoporosis)
Type 1 diabetes mellitus (T1DM) has been inconsistently associated with low bone mineral density (BMD) and increased fracture risk. 86 consecutive T1DM cases and 140 unrelated age and sex matched healthy nondiabetic controls were included in the study. After history and examination, BMD and body composition were assessed by dual energy X-ray absorptiometry (DXA). Serum samples were analyzed for calcium, phosphorus, albumin, creatinine, alkaline phosphatase, 25 (OH) vitamin D3, intact parathormone (PTH) levels (both cases and controls) and HbA1c, antimicrosomal and IgA tissue transglutaminase (IgA TTG) antibodies, cortisol, follicle stimulating hormone (FSH), testosterone, sex hormone binding globulin (SHBG), tetraiodothyronine (T4), thyroid stimulating hormone (TSH), growth hormone (GH), insulin-like growth factor-1 (IGF-1), and insulin-like growth factor binding protein 3 (IGFBP3) (cases only). T1DM cases had a lower BMD as compared to controls at both total body (TB) and lumbar spine (LS) (). Patients with celiac autoimmunity (CA) had significantly, lower BMD as compared to age, sex, and body mass index (BMI) matched T1DM controls. Linear regression analysis showed that low BMD in T1DM patients was associated with poor glycaemic control, lower IGF-1 levels, less physical activity (in total population as well as in male and female subgroups), and lower body fat percentage (in females) and higher alkaline phosphatase level (in males) ().